Cardiac Dysfunction in Severely Burned Patients: Current Understanding of Etiology, Pathophysiology, and Treatment. Issue 6 (June 2020) - Tapking, Christian; Popp, Daniel; Herndon, David N.; Branski, Ludwik K.; Hundeshagen, Gabriel; Armenta, Andrew M.; Busch, Martin; Most, Patrick; Kinsky, Michael P.
Abstract : ABSTRACT: Patients who experience severe burn injuries face a massive inflammatory response resulting in hemodynamic and cardiovascular complications. Even after immediate and appropriate resuscitation, removal of burn eschar and covering of open areas, burn patients remain at high risk for serious morbidity and mortality. As a result of the massive fluid shifts following the initial injury, along with large volume fluid resuscitation, the cardiovascular system is critically affected. Further, increased inflammation, catecholamine surge, and hypermetabolic syndrome impact cardiac dysfunction, which worsens outcomes of burn patients. This review aimed to summarize the current knowledge about the effect of burns on the cardiovascular system. A comprehensive search of the PubMed and Embase databases and manual review of articles involving effects of burns on the cardiovascular system was conducted. Many burn units use multimodal monitors (e.g., transpulmonary thermodilution) to assess hemodynamics and optimize cardiovascular function. Echocardiography is often used for additional evaluations of hemodynamically unstable patients to assess systolic and diastolic function. Due to its noninvasive character, echocardiography can be repeated easily, which allows us to follow patients longitudinally. The use of anabolic and anticatabolic agents has been shown to be beneficial for short- and long-term outcomes of burn survivors. Administration of propranolol (non-selective β-receptor antagonist) or oxandrolone (synthetic testosterone) for up to 12 months post-burn counteracts hypermetabolism during hospital stay and improves cardiac function. A comprehensive understanding of how burns lead to cardiac dysfunction and new therapeutic options could contribute to better outcomes in this patient population.